The Influence of Electronic Word of Mouth and Social Media Promotion on Consumers' Purchase Intention - Aditya, Rizal Bayu; Handayanto, Eko; Praharjo, Ardik (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This study aims to know the effect of electronic word of mouth and social media promotion on consumer purchase intention. The sampling technique used was purposive sampling with a total sample of 108 Momo Accessories consumers. The analytical tool used in this study is multiple regression analysis. The results of this study conclude that electronic word of mouth and social media promotion have a significant effect on consumer purchase intention. Apart from that, electronic word of mouth and social media promotions simultaneously and significantly influence consumer purchase intention.